Periodization for success - in-season external training loads relative to competition load in American football - Johnson, Q. R.; Yang, Y.; Cabarkapa, D.; Sealey, D.; Stock, S.; Gleason, D.; Frels, C.; Rink, M.; Fry, A. C. (Frontiers in Sports and Active Living, 2025)
Introduction: Despite an exponential development in performance monitoring technologies, the physical performance demands of sport remain an understudied topic in scientific literature. Thus, the primary purpose of this study was to quantify and compare the training loads (TL) of a collegiate American football team between in-season practices and official games by general position group, event type, and to assess the interaction between the two.